MINIMAX PROBLEM FOR THE ROMANOVSKY DISTRIBUTION IN THE Lγ METRIC - Yusupova A. K. (Web of Journals Publishing, 2025)
The article solves the minimax problem for the Romanovsky distribution in the Lj metric.Convergence theorems for variation of the Romanovsky distribution to normal, binomial,negative-binomial distributions, Poisson distributions, Erlang distributions, and betdistributions are given.
Keywords: Convergence by variation, Romanovsky distribution, normal, binomial, negativebinomial, Poisson, Erlang and Bet distributions.